'Broken hospital windows': debating the theory of spreading disorder and its application to healthcare organizations - Kate Churruca; Louise A. Ellis; Jeffrey Braithwaite (BMC, 2018)
Abstract Background Research in criminology and social-psychology supports the idea that visible signs of disorder, both physical and social, may perpetuate further disorder, leading to neighborhood incivilities, petty violations, and potentially criminal behavior. This theory of 'broken windows' has now also been applied to more enclosed environments, such as organizations. Main text This paper debates whether the premise of broken windows theory, and the concept of 'disorder', might also have utility in the context of health services. There is already a body of work on system migration, which suggests a role for violations and workarounds in normalizing unwarranted deviations from safe practices in healthcare organizations. Studies of visible disorder may be needed in healthcare, where the risks of norm violations and disorderly environments, and potential for harm to patients, are considerable. Everyday adjustments and flexibility is mostly beneficial, but in this paper, we ask: how might deviations from the norm escalate from necessary workarounds to risky violations in care settings? Does physical or social disorder in healthcare contexts perpetuate further disorder, leading to downstream effects, including increased risk of harm to patients? Conclusions We advance a model of broken windows in healthcare, and a proposal to study this phenomenon.